The Role of Renewable Energy Consumption Towards Carbon Neutrality in BRICS Nations: Does Globalization Matter? - Dingru, Liu; Ramzan, Muhammad; Irfan, Muhammad; Gülmez, Özge; Isik, Hayriye; Adebayo, Tomiwa Sunday; Husam, Rjoub (Frontiers in Environmental Science, 2021)
Although a number of studies have been conducted on the environmental Kuznets curve (EKC) and the pollution halo hypothesis (PHH), few researchers have assessed the scope in the light of the BRICS— Brazil, Russia, India, China, and South Africa—nations. Therefore, the current research assesses the income-induced EKC as well as the role of technological innovation and renewable energy consumption utilizing a dataset stretching from 1990 to 2018. The present research utilized the novel method of moments quantile regression (MMQR) developed by Machado and Silva (2019) to assess these interrelationships. The empirical outcomes from the MMQR affirmed an inverted U-shaped interrelationship between CO2 emissions and economic growth across all quantiles (first to ninth) for the BRICS nations, thus confirming the presence of the EKC hypothesis. Furthermore, we affirmed the PHH, thus confirming the negative interrelationship between globalization and ecological footprint across all quantiles (first to ninth). Moreover, it was found that renewable energy use plays a vital role in curbing the emissions of CO2 across all quantiles (first to ninth), while no evidence of significant connection was established between technological innovation and ecological footprint across all quantiles. In addition, the Granger causality outcomes revealed a feedback causality between income and ecological footprint, while a unidirectional causality was established from globalization and renewable energy use to ecological footprint.